2018
DOI: 10.3390/soc8040120
|View full text |Cite
|
Sign up to set email alerts
|

Migration as a Challenge to Couple Relationships: The Point of View of Muslim Women

Abstract: Migration posits new challenges to couple relationships. The distance from one’s family and kin, the need to restructure long-standing and culturally established role expectations, the social isolation, and economic strains often put couple stability at stake. Muslim women’s perception of the changes that have occurred to their couple relationship after migration has rarely been investigated. To fill this gap in the research literature, a sample of 15 Moroccan and as many Pakistani women living in Italy were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Migration-related disagreements between partners over their respective gender roles can increase tensions in the couple (Ben-David and Lavée 1994;Cheung 2008;Grzywacz et al 2009;Maciel, Van Putten, and Knudson-Martin 2009). For example, a qualitative study conducted by Accordini, Giuliani, and Gennari (2018) among migrant Muslim women to Italy revealed that the discovery of new gender roles values post-migration transformed their couple relationship. Couples that adjusted their respective values, roles and couple's way of life experienced greater intimacy and developed a more balanced couple relationship.…”
Section: Gender Role Valuesmentioning
confidence: 99%
“…Migration-related disagreements between partners over their respective gender roles can increase tensions in the couple (Ben-David and Lavée 1994;Cheung 2008;Grzywacz et al 2009;Maciel, Van Putten, and Knudson-Martin 2009). For example, a qualitative study conducted by Accordini, Giuliani, and Gennari (2018) among migrant Muslim women to Italy revealed that the discovery of new gender roles values post-migration transformed their couple relationship. Couples that adjusted their respective values, roles and couple's way of life experienced greater intimacy and developed a more balanced couple relationship.…”
Section: Gender Role Valuesmentioning
confidence: 99%
“…The results of the study suggest that, after migration, couples develop processes of maintenance, accommodation and cultural assimilation in establishing their couple relationships (Accordini, Giuliani & Gennari, 2018).…”
Section: Couple Relationships In the Immigrant Populationmentioning
confidence: 87%
“…To this end, a clear and well-defined coding grid was developed and the discriminant validity of the indicators was assessed. Our goal was to provide preliminary empirical evidence supporting the use of Conjoint Family Drawings in both research ( Accordini et al, 2018 ; Mannino et al, 2019 ) and clinical settings ( Gennari and Tamanza, 2017 ; Tamanza et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%